Сучасний стан археоботанічних досліджень в Україні - Пашкевич, Г.О. (Археологія і давня історія України, 2020)
Палеоетноботанічні дослідження, розпочаті в
Інституті археології АН УРСР в кінці 1970-х рр.
на пропозицію Д. Я. Телегіна, співпали з часом становлення палеоетноботаніки (археоботаніки) як
науки. За майже сорокарічний період досліджень
отримано для території України характеристику складу культурних рослин та супроводжуючих
бур’янів від неоліту до середньовіччя включно. Поява в останні десятиріччя в руках археоботаніків
Європи нового інструментарію (скануючий електронний мікроскоп), нових методів досліджень викопних решток рослин (хімічний аналіз мікрорешток за допомогою мас-спектрометра, генетичні
дослідження давніх ДНК, аналіз стабільних ізотопів та ін.) значно розширили результативність
вже опублікованих даних. The territory of Ukraine was the first on the path
of the Neolithic tribes to the territory of the East European
Plain. These tribes brought here cultivated
plants with the skills of their cultivation (hulled wheat,
barley, legumes) from the center of origin, from Asia
Minor through the Balkan Peninsula. N. I. Vavilov
considered that the territory of Ukraine together with
Moldova was one of the ancient places of farmers culture.
He received confirmation of his assumption about
the existence of crops of ancient hulled wheat in the
closed mountainous regions of the Carpathians. In
1940 he found a hulled wheat Triticum dicoccum in
the vicinity of the village of Putila near Chernivtsi.
Recently thanks to modern research and radiocarbon
dates on charred broomcorn millet grains Ukraine
has a gateway through which millet from China, the
birthplace of its origin, has spread to Europe. The earliest
radiocarbon date (1631—1455 cal BC) in Europe is
coming from the site Vinogradnyi Sad of Sabatynivka
culture, Bronze Age. This date was received thanks to
the European program «When and Where broomcorn
millet arrived in Europe». Reports of much earlier occurrences
of millet in Neolithic — Early Bronze Age
(6th — early 3rd millennium BC) were almost entirely
based on millet-looking impressions in pottery, daub
and figurines. A recent re-examination of these impressions
on figurines from the Usatovo culture with
using a scanning electron microscope excluded millet
grains as a source for some of the imprints. European
researchers show great interest in archaeobotanical
records of the crop from archaeological excavations of
the territory of Ukraine. The use of modern research
methods such as a scanning electron microscope, stable
isotope evidence, modernized radiocarbon dating,
chemical analysis of microparticles using a mass spectrometer,
and analysis of DNA will allow a new look at
the earliest obtained results.